PERAN PUBLIC RELATIONS SEBAGAI PENDUKUNG MANAJEMEN DI RUMAH SAKIT UMUM DR. PIRNGADI KOTA MEDAN - Hasibuan, Indah Kemala; Lubis, Rahmi (ANALITIKA, 2011)
The research is titled "The Role of Public Relations as a Management Support Hospital General Dr. Pirngadi Medan City "and discusses the role of public relations in order to improve the image of the hospital which describes the public relations image of the hospital to maintain (maintenance of image) and restore the image of the hospital (recovery of image) when carrying out its role as a supporter of management. This study aims to answer the problems that have been formulated. The detailed objectives of this study was to determine achievable extent of successful public relations duties to support the management to minimize patient complaints about inpatient services Jamkesmas participants in improving the image of the hospital in General Hospital Dr. Pirngadi Medan. The study population was inpatients General Hospital Dr. Pirngadi Jamkesmas Medan which is a participant during the month of January 2009 and aged 17 to 50 years. While the number of samples used to determine the Taro Yamane and using proportional random sampling technique. To answer the problems that have been formulated, used descriptive method with quantitative approach. From the analysis found the success rate of maintaining public relations image of the hospital by providing the best services at 65.12%, and restore the image of the hospital by providing the right solution for 62.79% proving that the role of public relations as a management support works.